BEYOND DIGITAL COMPETENCE: WHY AI-BASED VILLAGE FINANCIAL SYSTEMS FAIL TO PREVENT FRAUDULENT BEHAVIOR - Angin, Ria; Adawiyah, Putri Robiatul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The AI supported Village Financial System (Siskeudes) has been widely promoted as a tool for improving village financial governance and preventing fraud, yet whether improved digital competence actually translates into fraud prevention remains empirically unclear. This study aims to examine the effectiveness of technical guidance in enhancing the competence of village government apparatus and to assess its contribution to fraud prevention in village financial management. A qualitative case study approach was employed. Data were collected through in-depth interviews with seven village government officials and one village budget transparency activist in Jember Regency, and analyzed using thematic analysis involving data reduction, coding, categorization, and interpretation. The results show that technical guidance significantly improved the operational competence of officials who already possessed basic digital literacy, but increased competence did not automatically reduce fraud risk: Siskeudes minimizes administrative errors yet cannot detect intentional manipulation or systemic fraud, and weak institutional oversight leaves this gap open despite digital adoption. The novelty of this study lies in demonstrating that digital competence alone is insufficient for fraud prevention in village governance; effective mitigation instead requires an integrated framework combining digital financial systems, tiered capacity-building, institutional oversight by the Village Consultative Body (BPD), and community participation. The implication is that policymakers should shift from a technology centered approach toward an integrated governance strategy combining technological innovation, human resource development, and participatory accountability.